Race, labor, and violence in the delta: essays to mark the centennial of the Elaine massacre - Pierce, Michael C.; White, Calvin (University of Arkansas Press, 2022)
Black agricultural labor activism and white oppression in the Arkansas Delta: the cotton pickers' strike of 1891 / Matthew Hild -- "Night riding must not be tolerated in Arkansas": one state's uneven war against economic vigilantism / Guy Lancaster -- Black workers, white nightriders, and the Supreme Court's changing view of the Thirteenth Amendment / William H. Pruden III -- Henry Lowery lynching: a legacy of the Elaine Massacre? / Jeannie Whayne -- Black women, violence, and criminality in post-World War I Arkansas, 1919-1922 / Cherisse Jones-Branch -- Steadily holding our heads above water: the flood of 1927, white violence, and black resistance to labor exploitation in the Mississippi Delta / Michael Vinson Williams -- "Boss man tell us to get north": Mexican labor and Black migration in Lincoln County, Arkansas, 1948-1955 / Michael Pierce -- Sweet Willie Wine's 1969 walk against fear: Black activism and white response in east Arkansas fifty years after the Elaine Massacre / John A. Kirk -- "Sick and sinister": intersections of violence and the struggle for economic justice in the late twentieth century / Greta de Jong -- Evil in the Delta / Michael Honey.